The effects of 12-week baduanjin intervention on balance, isometric knee strength, gait biomechanics and risks of falls among elderly - Shihao, Xie (2025)
Physical function declines in older adults as they age, and failure to detect incorrect body postures or restore balance increases the likelihood of falls. Therefore, improving the balance function of the elderly has become an important goal in geriatric rehabilitation. Baduanjin is one of the traditional Chinese qigong treatment methods. Compared with other forms of exercise, it focuses more on the integration of body and mind, and improves the physical function of the elderly and various clinical populations. However, previous studies on Baduanjin have only used subjective scales that indirectly assess fall risk. The effects of Baduanjin on gait biomechanics and balance in older adults is unknown. Therefore, this study evaluated the impact of 12 weeks of Baduanjin on the risk of falls from all aspects, including balance, isometric knee joint strength, and gait parameters. After screening, the 42 participants were divided into groups by drawing lots through the blind box with two kinds of paper strips: B and C. They were randomly divided into one of the following conditions: 1. Baduanjin group (n=22), 2. control group (n=20). The intervention period was 12 weeks, with balance, isometric knee joint strength, and gait tests conducted in the first, sixth, and twelfth weeks, respectively. Also, after the intervention, the biomechanical parameters of eight sections of the Baduanjin were evaluated. Based on the research results, we conclude that compared to walking intervention of the same intensity, the Baduanjin intervention can effectively improve the sway path (37.62±9.73% vs 10.12±0.66%, p<0.05), sway velocity (19.06±10.73% vs 0.96±1.40%, p<0.05), sway area (31.54±11.73% vs 24.95±5.47%, p<0.05) and sway amplitude (29.16±12.44% vs 5.63±1.69%, p<0.05) during balance test in the coronal plane of the elderly. In addition, Baduanjin intervention can improve the gait symmetry during early (50.00±67.08% vs 20.00±84.85%, p<0.05) and mid stance phases (55.56±46.64% vs 11.11±82.22%, p<0.05) and maximum strength of knee extensor (7.77±1.69% vs 3.39±1.44%, p<0.05). In conclusion, compared to conventional walking intervention, the Baduanjin intervention is more conducive in improving the balance and gait stability of elderly, possibly due to the increase in lower limb muscle strength.